Targeting Structural Change for HIV Prevention: A Process and Tool for Community Application. Issue 6 (November 2015) - Willard, Nancy; Chutuape, Kate; Stewart-Campbell, Rachel; Boyer, Cherrie B.; Ellen, Jonathan
To address the persistent HIV epidemic in the United States, prevention efforts are focusing on social determinants related to HIV risk by targeting systems and structures, such as organizational and institutional policies, practices and programs, and legislative and regulatory approaches to modify features of the environment that influence HIV risk. With limited evidenced-based examples, communities can benefit from strategic planning resources that help them consider developing structural-level changes that target root causes of HIV risk. In this article, we present the Connect to Protect® project that outlines a process and a tool to move from general ideas to specific structural changes. Examples from 14 coalitions are also provided. Using the process and tools presented here can provide a launching pad for other coalitions seeking to build an HIV prevention agenda and for practitioners seeking to incorporate structural changes for community health promotion.